A novel modeling method for fiber-based progressive collapse analysis of composite frames. (October 2022) - Zheng, Yu-hui; Zhong, Wei-hui; Tan, Zheng; Meng, Bao; Duan, Shi-chao
Highlights: An Efficient numerical method for fiber-based progressive collapse analysis of composite frames was provided. The component-based method was employed to simplify beam-to-connection in OPENSEES. Composite relationship between beam and slab and damage evolution of materials were considered. Parameter analysis using fiber-based models. Abstract: To fully take into account the computational efficiency and accuracy of the numerical model for anti-collapse analysis. In this paper, a fiber-based model composed of zero-length elements and nonlinear beam-column elements was established considering the composite relationship between the beam and slab and the damage evolution of the material. The beam-to-column connection was reasonably simplified by employing a component-based method, and an efficient numerical method was developed based on OpenSees. A comparison with experimental data indicated that the fiber-based model accurately reflected the nonlinear mechanical behavior of the composite beam-column assemblies, and showed excellent computational efficiency. Because the component-based models of different beam-to-column connections have been proposed and further improved, the proposed modeling method can be conveniently applied to the anti-collapse analysis of composite frames with different connections. In addition, some design suggestions obtained through a parameter analysis were given to prevent the development of a chain reaction.